2016
DOI: 10.21873/anticanres.11079
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic Acid Suppresses Hepatitis B Virus X Protein-mediated Autophagy and Chemotherapeutic Drug Resistance

Abstract: Hepatitis B virus X (HBx) protein is a multifunctional oncoprotein that affects diverse cell activities via regulation of various host cell signaling pathways. The current investigation demonstrated that ursolic acid (UA), a pentacyclic triterpenoid, protected hepatoma cells and reduced HBx-mediated autophagy through modulation of Ras homolog gene family member A (RhoA). Low-level ectopic HBx expression in Huh7 cells induced more significant autophagosome formation than high-level HBx expression. HBx activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…[26][27][28][29] The current investigation demonstrated that ursolic acid could protect hepatoma cells and reduce HBx-mediated autophagy through modulation of Ras homolog gene family member A (RhoA). 26 In the present study, it was found that ursolic acid at the low micromolar range may promote its anticancer action by targeting glycolysis in phenotypically distinct breast cancer cells. 27 Ursolic acid can also inhibit proliferation and induce apoptosis of human osteosarcoma 143B cells by inactivating Wnt/β-catenin signaling.…”
Section: Antitumor Activitymentioning
confidence: 89%
“…[26][27][28][29] The current investigation demonstrated that ursolic acid could protect hepatoma cells and reduce HBx-mediated autophagy through modulation of Ras homolog gene family member A (RhoA). 26 In the present study, it was found that ursolic acid at the low micromolar range may promote its anticancer action by targeting glycolysis in phenotypically distinct breast cancer cells. 27 Ursolic acid can also inhibit proliferation and induce apoptosis of human osteosarcoma 143B cells by inactivating Wnt/β-catenin signaling.…”
Section: Antitumor Activitymentioning
confidence: 89%
“…Several studies have shown that UA possesses anti-proliferative, pro-apoptotic, anti-inflammatory, anti-metastatic, and antiangiogenic properties against cancer cells [17][18][19][20][21][22][23]. UA inhibits cell proliferation, arrests cell cycle progression, and reduces tumorigenesis through multiple signaling pathways [24][25][26][27][28][29][30][31][32][33]. Pentacyclic triterpenoid compounds have been found to display their anticancer properties by altering the levels of reactive oxygen species (ROS), derivatives of oxygen metabolism that are generated under conditions of cellular oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Pada masa pandemi Covid-19 penemuan senyawa atau tanaman obat tradisional yang berpotensi sebagai antivirus dan imunomodulator terus dilakukan dan berdasarkan hasil penelitian senyawa yang terkandung dalam tanaman kumis kucing berpotensi sebagai inhibitor Covid-19 (Sarkar & Das ;Rowaiye et al, 2020;Sekiou et al, 2020;Adem et al, 2020;Dahab et al, 2020;Narkhede et al, 2020;Sharma & Kaur, 2020;Faramayuda et al, 2021), antiherpetik (Ikeda et al, 2011;Medini et al, 2016;Astani et al, 2011;Astani & Schnitzler, 2014;Bourne et al, 1999;Benencia & Courreges, 2000;Sharifi-Rad et al, 2018), anti-human immunodeficiency virus (HIV) (Lin et al, 1999;McDougall et al, 1998;Zhang et al, 2014;Mengoni et al, 2002;Kashiwada et al, 1998;Xu et al, 1996), anti hepatitis (Haid et al, 2012;Duan et al, 2016;Kong et al, 2013;Chang et al, 2016) dan imunomodulator (Harun et al, 2015;Woottisin et al, 2011;Friedman, 2015;Kim et al, 2008;Takano et al, 2004;Sanbongi et al, 2004;Youn et al, 2003).…”
Section: Pendahuluanunclassified